2014
DOI: 10.1057/gpp.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Microinsurance Demand

Abstract: The purpose of this article is to structure the extant knowledge on the determinants of microinsurance demand and to discuss unresolved questions that deserve future research. To achieve this outcome, we review the academic literature on microinsurance demand published between 2000 and early 2013. The review identifies 12 key factors affecting microinsurance demand: price, wealth, risk aversion, non-performance risk, trust and peer effects, religion, financial literacy, informal risk sharing, quality of servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…Why households decide to insure is currently a highly explored topic. Next to purely economic aspects, social and cultural influences such as risk aversion and influence from peers or personal and demographic factors such as age and gender are also considered being important [4,42]. Explicitly including reasons behind the decision to insure is therefore out of the scope of this paper.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why households decide to insure is currently a highly explored topic. Next to purely economic aspects, social and cultural influences such as risk aversion and influence from peers or personal and demographic factors such as age and gender are also considered being important [4,42]. Explicitly including reasons behind the decision to insure is therefore out of the scope of this paper.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In particular, if households had different financial resources, the decision to insure and potential changes in transfer behavior could be included into the model in more detail. When limited economic means alone inhibit some households from purchasing insurance [4,42], uninsured households would on average have lower assets at their disposal which might increase their dependence on informal support. Given the different characteristics of the shock events this could have various consequences.…”
Section: Plos Onementioning
confidence: 99%
“…It has therefore been suggested that to determine the demand for crop insurance including weather index-based insurance (WII), it is important to assess the frequency and impact of key weather-related perils and the mitigation strategies used by affected farmers (Barnett and Mahul, 2007;McCord, 2011), and the willingness of farmers to participate and pay for such insurance products (Barnett and Mahul, 2007). Other studies have also emphasised that the demand for micro-insurance products including WII depends on a combination of farmers' economic (price, wealth and income), social (risk, trust and financial literacy), structural (informal risk sharing, risk exposure) and personal (age, gender) factors (Eling et al, 2014;Fiala, 2017). Besides these, institutional factors such as a farmer's access to extension services have been reported to influence the uptake of agricultural insurance (Ali, 2013;Wairimu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…What early research on participation in micro-insurance shows is that households appear to not purchase enough of it (Eling, Pradhan, and Schmit, 2014;Bock and Gelade, 2012). The research, which is mostly in the form of randomised control trials, finds that insurance purchase is constrained by price, trust, liquidity constraints and limited salience (Giné, Townsend, and Vickery, 2008;Cole, Giné, et al, 2013).…”
Section: The Research Settingmentioning
confidence: 99%
“…Despite the importance that policy has given micro-insurance in improving financial access for low income households, studies show that households are yet to sufficiently adopt these products (Eling, Pradhan, and Schmit, 2014;Bock and Gelade, 2012). In this paper, we address a natural follow-up question: when households do purchase insurance, do they return to renew it?…”
Section: Introductionmentioning
confidence: 99%